2022
DOI: 10.3389/fimmu.2022.965120
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application status and prospect of the combined anti-tumor strategy of ablation and immunotherapy

Abstract: Image-guided tumor ablation eliminates tumor cells by physical or chemical stimulation, which shows less invasive and more precise in local tumor treatment. Tumor ablation provides a treatment option for medically inoperable patients. Currently, clinical ablation techniques are widely used in clinical practice, including cryoablation, radiofrequency ablation (RFA), and microwave ablation (MWA). Previous clinical studies indicated that ablation treatment activated immune responses besides killing tumor cells di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…There has been longstanding interest in the capacity of ablation to activate tumor-directed immune responses. Measurable and occasionally abscopal anti-tumor immune responses have been observed with cryoablation, radiofrequency ablation and radiation, largely when used in combination with immunomodulatory agents like CpG or pro-inflammatory cytokines (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). We recently reported that histotripsy, a non-thermal mode of mechanical FUS ablation (32-36), stimulates potent local and abscopal CD8+ T cell infiltration and tumor inhibition as monotherapy; using murine models of melanoma and hepatocellular carcinoma, we observed that this effect can enhance checkpoint inhibition immunotherapy (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been longstanding interest in the capacity of ablation to activate tumor-directed immune responses. Measurable and occasionally abscopal anti-tumor immune responses have been observed with cryoablation, radiofrequency ablation and radiation, largely when used in combination with immunomodulatory agents like CpG or pro-inflammatory cytokines (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). We recently reported that histotripsy, a non-thermal mode of mechanical FUS ablation (32-36), stimulates potent local and abscopal CD8+ T cell infiltration and tumor inhibition as monotherapy; using murine models of melanoma and hepatocellular carcinoma, we observed that this effect can enhance checkpoint inhibition immunotherapy (37).…”
Section: Discussionmentioning
confidence: 99%
“…There is great interest in developing ablative therapies to trigger systemic anti-tumor immune responses that could augment the efficacy of cancer immunotherapy (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). By initiating immunogenic cell death pathways (e.g., necroptosis, pyroptosis) that release tumor-specific antigens within the context of pro-inflammatory danger signals, ablation could initiate the cancer immunity cycle of antigen presentation and adaptive immune stimulation (14).…”
Section: Introductionmentioning
confidence: 99%
“…This produces tissue-heating effects, which cause cellular death by coagulative necrosis. This technique has established safety and efficacy profiles in the management of tumors, including liver, lung, kidney, thyroid, and breast [54 ▪ ]. Microwave ablation has also been shown to be safe and effective in high-risk locations, such as for ablation of liver lesions near the heart [55 ▪ ].…”
Section: Microwave Ablationmentioning
confidence: 99%
“…Tumor cell fragments contribute to antigen‐presenting cell (APC) maturation and dendritic cell infiltration thereby promoting antitumor immunity. These fragmented tissues act as new antigens, stimulating an increase in the T cell‐based immune response while decreasing the number of Treg cells that regulate immunosuppression 71,72 . In post‐thermal ablation studies of various cancers such as liver and pancreatic cancer, it was found that increased infiltration of CD4+ and CD8+ T cells and decreased proportion of Treg cells in the immune environment after RFA attenuated the immunosuppressive effect in the tumor microenvironment 73 .…”
Section: Combination Of Rfa With Targeted Therapy and Immunotherapymentioning
confidence: 99%